Environmental, Social, Governance (ESG) pada Kinerja Perusahaan denganBoard Gender Diversity sebagai Pemoderasi - Ulfa, Siti Naziyatul; Rahman, Annisaa (ITB AAS Indonesia Surakarta, 2024)
Companies need to build good relationships with stakeholders by meeting the demands of stakeholders which are the company's efforts to maintain good company performance. One of the company's efforts to build a good relationship with stakeholders is by disclosing transparent information. Currently, more and more companies want to provide a clear picture of corporate practices and responsibilities, one of which is by disclosing environmental, social and corporate governance (ESG) aspects. The purpose of this study is to provide empirical evidence regarding the influence of Environmental, Social, and Governance (ESG) on company performance and provide empirical evidence regarding the role of board gender diversity on the influence of ESG on the performance of companies listed on the Stock Exchange in Indonesia for the period 2018-2022. The sampling technique in this study was purposive sampling. The results of this study found that ESG has a positive effect on company performance and board gender diversity plays a role in encouraging ESG activities to improve company performance in Indonesia.